Desensitization of the mu-opioid activation of phospholipase C in SH-SY5Y cells: the role of protein kinases C and A and Ca(2+)-activated K+ currents. - Smart, D. (1995)
1. In SH-SY5Y cells, mu-opioids cause a rapidly desensitizing activation of phospholipase C (PLC), that appears secondary to Ca2+ influx via L-type voltage-sensitive Ca2+ channels (VSCCs). The aim of the present study was to characterize the mechanisms of desensitization of the mu-opioid-induced inositol (1,4,5) triphosphate (Ins(1,4,5)P3) response, by use of a stereospecific radioreceptor mass assay. 2. (R+)-Bay K 8644 (1 nM-10 microM) dose-dependently inhibited fentanyl-induced Ins(1,4,5)P3 formation, with an IC50 of 28.5 nM, confirming our earlier observations that mu-opioids open L-type VSCCs, thus allowing Ca2+ influx to activate PLC. 3. Ro 31-8220 (0.1 nM-10 microM), a protein kinase C inhibitor, dose-dependently enhanced fentanyl-induced Ins(1,4,5)P3 formation (EC50 = 20.0 nM), whilst acute phorbol 12,13-dibutrate (1 microM) abolished the response. 4. H-89 (1 nM-10 microM), a protein kinase A inhibitor, also dose-dependently enhanced fentanyl-induced Ins(1,4,5)P3 formation (EC50 = 93 nM), whilst dibutryl cyclic AMP (0.5 mM) abolished the response. 5. Blockade of Ca(2+)-activated K+ currents with 4-aminopyridine (2 mM) or iberiotoxin (10 nM) had no effect on fentanyl-induced Ins(1,4,5)P3 formation but further increased the Ro 31-8220-enhanced response. 6. All three mechanisms had additive, or even supra-additive, effects, but only at later (120-300 s) time points. In addition, fentanyl-induced Ins(1,4,5)P3 formation, even if enhanced by H-89, Ro 31-8220 and/or 4-aminopyridine, was inhibited by nifedipine (1 nM-10 microM). 7. In conclusion, desensitization of the mu-opioid-induced activation of PLC is multifactorial, involving protein kinases C and A and Ca(2+)-activated K+ efflux, but the L-type VSCC is of critical importance and may be a possible common site of action.